High school student's mathematical modeling skills in open-ended learning. (March 2020) - Damayanti, U; Hartono, Y; Hiltrimartin, C; Indaryanti
Abstract: This research is a descriptive study aims to determine the mathematical modeling skills of students after using the open-ended learning to algebraic arithmetic operations in class VII SMP Negeri 17 Palembang. The subjects of this study were grade VII.6 students of SMP Negeri 17 Palembang with 32 students. The learning process is adapted to the stages of the open-ended learning. On the student worksheet, the problem given is an open-ended problem. The researcher also uses problem-solving questions during the evaluation test. Data collected using tests. The results of this study indicate that the mathematical modeling skill of students in open-ended learning in class VII.6 in SMP Negeri 17 Palembang is categorized good with an average of 78.54%. Students who are still lacking in modeling mathematical problems because they still incorrectly understand the problem and draw up a problem-solving plan.